MENGUJI ASAS DROIT DE SUITE DALAM JAMINAN FIDUSIA - Sarjana, I Made; Dewi Kasih, Desak Putu; Kartika, I Gusti Ayu (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 4 No 3 (2015)DO - 10.24843/JMHU.2015.v04.i03.p01, 2015)
The principle of droit de suite is one of the most important principles in the law of guarantee, especially in fiduciary security. The principle implies that the rights of the creditor as the recipient of the fiduciary objects continue to follow the object of guarantee, wherever the object is, to guarantee the repayment of the debts of the debitor. The rights which are owned by the creditor as the recipient of fiduciary security in the principle seem to be absolute, but in fact if it is related to de practice, the principle of droit de suite has certain limitations. The limitations of this principle is whon it is faced with higher interest, the individual rights owned by the recipient of fiduciary must succumb, as in the case of illegal logging, which once was decided to test the Forestry Law by the Constitutional Court (Case Decision Number 012/PUU-III/2005). Although the State can perform fiduciary deprivation of the object which is used for committing illegal logging, but from the aspect of material criminal law, it cannot be done immediately to destroy the object of guarantee, since object of the fiduciary collateral, is not considered a dangerous thing. Whereas, from the legal aspects of criminal procedure, if the case has been decided, then there is a duty of the State to return the object of fiduciary to those who own it. From the aspect of civil law, the creditor as recipient of fiduciary who feel harmed as a result of illegal logging practices may have standing to sue for damages under Article 1365 of Burgerljik Wetboek. The provision is used, because the act of illegal logging is an act against the law and there are losses caused to the recipient of fiduciary.
Keywords: principle of droit de suite, fiduciary, limitations.